Somatic cell count, electrical conductivity and biochemical parameters in mastitis milk in cows - Yildiz, H.; Kaygusuzoglu, E.; Simsek, H. (Indian Veterinary Journal, 2006)
Subclinical mastitis can be diagnosed bacteriologically or with some biochemical parameters (Na, K, Cl, lactose and proteins), electrical conductivity (EC), total bacterium counts, somatic cell counts (SCC), California Mastitis Test (CMT) of the milk (Charjan et al., 2000-1 Pednekar et al., 1992). It has been reported (Kitchen et al., 1980; Charmings et al., 1984) that infection changes the permeability of the vessels in udder tissue which causes an increase in Na and Cl levels and leucocytes number but a decrease in K level, lactose and fat rates, that leads to an elevation in SCC and EC. The aim of this study is to find out the relationship between SCC, EC, Na and K levels in the milk of the cows with subclinical mastilis.
Keywords: Tests